Heat Transfer Performance and Influencing Factors of Waste Tires During Pyrolysis in a Horizontal Rotary Furnace - Hongting Ma; Yang Bai; Shuo Ma; Zhipeng Zhou (Energies)
Pyrolysis technology currently serves as a significant method for recycling and reducing waste tires. In this paper, in order to improve the heat transfer efficiency during the pyrolysis of waste tires in a horizontal rotary furnace and the yield of pyrolysis oil, the effect laws of tire particle size, rotary furnace rotation speed, enhanced heat transfer materials, and adding spiral fins on heat transfer performance and pyrolysis product distribution were studied, respectively. The innovation lies in two aspects: first, aiming at the problems of slow heat transfer and low pyrolysis efficiency in horizontal rotary furnaces, we identified technical measures through experiments to enhance heat transfer, thereby accelerating pyrolysis and reducing energy consumption; second, with the goal of increasing high-value pyrolysis oil yield, we determined optimal operating parameters to improve economic and sustainability outcomes. The results showed that powdered particles of waste tires were heated more evenly during the pyrolysis process, which increased the overall heat transfer coefficient and the proportion of liquid products. When the rotational speed of the rotary pyrolysis furnace exceeded 2 rpm, there was sufficient contact between the material and the furnace wall, which was beneficial to the improvement of heat transfer performance. Adding heat transfer enhancement materials such as carborundum and white alundum could improve the heat transfer performance between the pyrolysis furnace and the material. Notably, a rotational speed of 3 rpm and carborundum were used as a heat transfer enhancement material with powdered waste tire particles during the pyrolysis process; the overall heat transfer coefficient was the highest, which was 16.89 W/(m2·K), and the proportion of pyrolysis oil products was 46.1%. When spiral fins were installed, the comprehensive heat transfer coefficient was increased from 12.78 W/(m2·K) to 16.32 W/(m2·K). The experimental results show that by increasing the speed of the pyrolysis furnace, adding heat transfer enhancing materials with high thermal conductivity to waste tires, and appropriate particle size, the heat transfer performance and pyrolysis rate can be improved, and energy consumption can be reduced.